The wild things : a novel - Eggers, Dave (McSweeney's, 2009)
During a fight at home, young Max flees and runs away into the woods. He finds a boat there, jumps in, and ends up on the open sea, destination unknown. He lands on the island of the Wild Things, and soon he becomes their king. But things get complicated when Max realizes that the Wild Things want as much from him as he wants from them. Based loosely on the storybook by Maurice Sendak and the screenplay co-written with Spike Jonze.